Does Extraesophageal Reflux Support the Development of Lung Adenocarcinoma? Analysis of Pepsin in Bronchoalveolar Lavage in Non-Smoker Patients - Zemanova, Petra; Vocka, Michal; Vanickova, Zdislava; Liska, Frantisek; Krizova, Ludmila; Kalab, Josef; Votruba, Jiri (Cancers, 2024)
The significance of extraesophageal reflux as a risk factor in lung adenocarcinoma has been understudied. In this study, we investigated whether extraesophageal reflux leads to higher pepsin concentrations in bronchoalveolar lavage (BAL) in patients with lung adenocarcinoma compared to controls. Subjects were recruited from non-smoker patients (lifelong non-smokers and ex-smokers with more than 5 years of non-smoking history) who had undergone bronchoscopy due to pulmonary abnormalities on a CT scan and met the inclusion criteria. Based on histological verification of the lung process, the patients were divided into three groups: (1) lung adenocarcinoma, (2) pulmonary metastases, and (3) lung sarcoidosis. Lung adenocarcinoma cases were further categorized as central or peripheral. BAL samples collected during bronchoscopy were quantitatively analyzed by enzyme-linked immunosorbent assay (ELISA) to measure pepsin levels. No statistically significant difference in pepsin concentration was observed between the lung adenocarcinoma group and control groups (p = 0.135). After excluding hemorrhagic BAL samples, the pepsin concentration was significantly the lowest in patients with lung adenocarcinoma (p = 0.023) compared to the control groups. The results of the study do not support the hypothesis of a higher occurrence of extraesophageal reflux (evaluated as the amount of pepsin in BAL) in non-smoker patients with lung adenocarcinoma.